2020
DOI: 10.1016/j.ejso.2019.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk score for prediction of long-term outcomes after hepatectomy for intrahepatic cholangiocarcinoma: Report of a collaborative, international-based, external validation study

Abstract: A preoperative risk score (PRS) to predict outcome of patients with intrahepatic cholangiocarcinoma treated by liver surgery could be clinically relevant. To assess accuracy for broadly adoption, external validation of predictive models on independent datasets is crucial. The objective of this study was to externally validate the score for prediction of long-term outcomes after liver surgery for intrahepatic cholangiocarcinoma proposed by Sasaki et al. and based on preoperative albumin, neutrophil-to-lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Combining the PRS score and the 8th AJCC staging can correct the problem of overlapping overall survival in T2, T3, and T4 categories and classify ICC patients with sufficient prognostic difference. 37 Cancer biomarkers, such as cancer stem cell markers (CD44v6, 8-10, CD133, EpCAM, and ALDH1A1), are also favored to enhance capacity for prognostication of CCA and have been used as additional factors for prediction of recurrence in early-stage disease. 35 Similarly, our study showed that the 8th edition did not satisfactorily classify the prognosis of iCCA in the Thai OV.-associated CCA cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the PRS score and the 8th AJCC staging can correct the problem of overlapping overall survival in T2, T3, and T4 categories and classify ICC patients with sufficient prognostic difference. 37 Cancer biomarkers, such as cancer stem cell markers (CD44v6, 8-10, CD133, EpCAM, and ALDH1A1), are also favored to enhance capacity for prognostication of CCA and have been used as additional factors for prediction of recurrence in early-stage disease. 35 Similarly, our study showed that the 8th edition did not satisfactorily classify the prognosis of iCCA in the Thai OV.-associated CCA cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of tumor size in ICC staging has also been debated. [25][26][27] In fact, tumor size was not included in the first ICC staging system in the 7th edition manual, only being added to the 8th edition. 6 Currently, a single tumor 5 cm and a solitary lesion >5 cm with no vascular invasion are classified as T1a and T1b disease, respectively, in the 8th edition of AJCC staging.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic stratification scores for survival after resection of different malignancies, including ICC, have been published in recent years to optimize perioperative decision making [29][30][31][32]. We have recently introduced the RSI, estimating the future functional liver remnant with respect to the preoperative liver function and the expected or actual extent of hepatic surgery, as an independent risk factor for survival after resection of hepatocellular carcinoma and colorectal liver metastases [11,12].…”
Section: Discussionmentioning
confidence: 99%